Theoretical research of horizontal rotor machine dynamics. - Ткачук, В.П.; Савицький, Ю.В. (Problems of Tribology, 2016)
The rotor system on the example of washing machine with horizontal rotation axis is examined and theoretical re-search using linear oscillation theory is realized. The analysis of experimental results is realized and requirements for design-ing rotor machines with low vibroactivity are formulated.Keywords: dynamics of тоtоr machines, washing-machine, vibro-activity.